(untitled) (Academic journal Industrial Machine Building Civil Engineering, 2017)
Optimization model was designed and analyzed; it allowed to determine the best geometry of the mechanical centrifugal unbalance vibration exciter by the impact on the overall dynamic performance of vibration exciter; optimization problem is solved with condition of identical material consumption; according to the results formulated conclusions. Keywords: centrifugal force of inertia unbalance of vibration exciter, shape of the unbalance; controlled mechanical centrifugal unbalanced vibration exciters of oscillations, optimization mathematical model, the objective (target) function, permissible limit, optimal values, materials consumption.